2022
DOI: 10.37990/medr.1031528
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Neuro-Linguistic Programming on Depression, Anxiety and Stress in Liver Transplant Patients

Abstract: Aim: This study was conducted using a prospective randomized single-blind clinical trial model to examine the effect of neurolinguistic programming (NLP) on depression, anxiety, and stress in liver transplant patients. Materials and Methods: This study was conducted with liver transplant patients at a university's Liver Transplant Institute between June 2021 and December 2021. The sample size of the study was determined as 84 (Experimental group: 42, control group: 42). Personal information form and Depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In addition, it is seen that the burden of caregiver mothers with low perceived economic status is higher. When the literature is examined in Türkiye, Türe et al found that the low income level of mothers with children with chronic illnesses affected the burden of care, Doğan et al found that the burden of care of caregivers experiencing economic difficulties was significantly moderate to severe [34,35]. The higher burden of caregiving scores of families with poor economic status may be considered to increase the burden that mothers, who are already physically, socially and emotionally challenged, have to cope with by adding the financial difficulties they experience in meeting the basic needs of their children.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is seen that the burden of caregiver mothers with low perceived economic status is higher. When the literature is examined in Türkiye, Türe et al found that the low income level of mothers with children with chronic illnesses affected the burden of care, Doğan et al found that the burden of care of caregivers experiencing economic difficulties was significantly moderate to severe [34,35]. The higher burden of caregiving scores of families with poor economic status may be considered to increase the burden that mothers, who are already physically, socially and emotionally challenged, have to cope with by adding the financial difficulties they experience in meeting the basic needs of their children.…”
Section: Discussionmentioning
confidence: 99%
“…NLP operates as a set of techniques rather than a theoretical framework. Its primary aim is to address learners' challenges, including fear, habit disorders, learning difficulties, anxiety, sadness, and depression [4,5] . This technique is designed to help individuals overcome their limitations by identifying and modifying restrictive behavior, ultimately enabling them to achieve their learning goals.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several treatments for psychological problems, non-drug methods such neuro-linguistic programming (NLP) have started to attract attention in recent years [ [13] , [14] , [15] ]. People want to have control over their own lives [ 16 ]. With NLP, the individual realizes their existing power.…”
Section: Introductionmentioning
confidence: 99%